English Joachite Manuscripts and Medieval Optimism about the Role of the Jews in History: A List for Future Studies - Kerby-Fulton, Kathryn (Florilegium, 2006)
This article contains the first ever published list of Joachite manuscript sources in England, with an introductory overview of the main ideas, usually optimistic, which such texts transmitted. The list is offered to supplement on-going work in Judaism and Insular culture.